2007
DOI: 10.1097/01.pai.0000213122.66096.f0
|View full text |Cite
|
Sign up to set email alerts
|

Cell Membrane Reactivity of MIB-1 Antibody to Ki67 in Human Tumors: Fact or Artifact?

Abstract: Ki67 immunohistochemistry is a widely used marker of the tumor proliferative fraction. Apart from the nuclear staining of dividing cells, MIB-1 monoclonal antibody was also found to stain the cell membrane of some tumor types. Indeed, such membrane reactivity was proposed as a diagnostic feature of hyalinizing trabecular tumor (HTT) of the thyroid. To verify the diagnostic role of Ki67 membrane pattern, 6 HTTs, 8 pulmonary sclerosing hemangiomas (SH), and 6 other human tumors with MIB-1 cell membrane immunorea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
63
1
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 19 publications
(15 reference statements)
5
63
1
4
Order By: Relevance
“…MIB-1 staining pattern is useful as the membrane-positive reactivity is a distinctive feature of HTT, however, no such pattern appears in PTC. Notably, it has been reported that the membrane-positive pattern is observed for the MIB-1 clone only but not other clones of Ki-67, which was also confirmed in our present study (16).…”
Section: Discussionsupporting
confidence: 80%
“…MIB-1 staining pattern is useful as the membrane-positive reactivity is a distinctive feature of HTT, however, no such pattern appears in PTC. Notably, it has been reported that the membrane-positive pattern is observed for the MIB-1 clone only but not other clones of Ki-67, which was also confirmed in our present study (16).…”
Section: Discussionsupporting
confidence: 80%
“…Based on bioinformatics prediction, the binding site for LINC01260 and CARD11 were present in the CARD11 3' untranslated region (UTR), with a free energy between of ΔG = -76. 38 and ΔG/n = -0.066. Therefore, CARD11 was confirmed as a target gene for LINC01260.…”
Section: Linc01260 Inhibits Card11 Activitymentioning
confidence: 99%
“…The aberrant staining pattern was not identified in other thyroid tumours [5][6][7], and other Ki-67 clones, such as 7B11, KIS5, KI88, and SP6, did not show this phenomenon [3,8]. Therefore, immunostaining for MIB-1 has been generally used in diagnosing HTT.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the aberrant staining pattern is also observed in breast carcinoma [9], salivary gland pleomorphic adenoma [10], and pulmonary sclerosing hemangiomas [11], but no diagnostic significance has been demonstrated. Leonardo et al described that crossreactivity of MIB-1 monoclonal antibody with a cell membrane epitope seems the most likely explanation for the findings [8].…”
Section: Discussionmentioning
confidence: 99%